A continent ileostomy device. - Pemberton, J H (1983)
The feasibility of achieving fecal continence by mechanical occlusion of an end-ileostomy is explored. Accordingly, progressive stomal occlusion with an indwelling occluding device was evaluated in four healthy patients with Brooke ileostomies. Pre-occlusion clinical and physiologic tests were done, including fat balance, intestinal transit time, ileal motility and absorption, ileal compliance, ileal radiography, and ileoscopy. Progressive stomal occlusion was then employed until periods of occlusion of 5 to 8 hours were achieved after 10 to 16 weeks. Pre-occlusion tests were then repeated. Patients mastered use of the occluding device rapidly, and the device achieved reliable stomal continence in each patient. Whereas ileal capacity was small initially, intermittent occlusion resulted in a large, capacious ileal reservoir. Fasting ileal motility was increased slightly by stomal occlusion, although intestinal transit during feeding was not altered. Also, ileal absorption of glucose, electrolytes, vitamin B-12, and fat were not changed, and ileal mucosa at the site of occlusion remained intact endoscopically. The authors concluded that chronic intermittent occlusion of a Brooke ileostomy with an indwelling stomal device achieved enteric continence without impairing intestinal function.